Internet linguistics as an independent field of the study of language: review of main directions and concepts - D. S. Borisova (Вестник Самарского университета: История, педагогика, филология)
Over the recent decades the study of Internet language has been of considerable interest to linguists, which is explained by the growing popularity of social networks and the emergence of new forms of communication with the use of information technology. With this considerable interest the need to analyze existing literature in order to identify the directions and difficulties that researchers face is particularly relevant. This work presents an analysis of the main research areas in the field of Internet linguistics present both in Russia and other countries. In order to do this the goals of this paper include studying the history of Internet linguistics and identifying the main terms of this field. The subject of the study is defined as Internet linguistics. The study examined works in Russian and English aimed at studying Internet communication and Internet language. The results of the study showed that in a relatively short period of time, Internet linguistics as an independent field has acquired a significant number of works, including both theoretical issues of defining the concepts of Internet communication and Internet language, as well as highlighting their characteristic features, and a more substantive analysis of individual aspects of Internet language or the use of Internet technologies to study language in general as well as practical application of linguistic knowledge in the Internet. Despite the large number of works within this field, the terms in Internet linguistics still lack definition which has been accepted by the majority of researchers and is extremely variable, which emphasizes the need for further in-depth study and development of the theoretical basis of this direction